Deep Brain Stimulation Effects on Gait Pattern in Advanced Parkinson’s Disease Patients - Navratilova, Daniela; Krobot, Alois; Otruba, Pavel; Nevrly, Martin; Krahulik, David; Kolar, Petr; Kolarova, Barbora; Kaiserova, Michaela; Mensikova, Katerina; Vastik, Miroslav; Kurcova, Sandra; Kanovsky, Petr (Frontiers in Neuroscience, 2020)
Background Gait disturbance accompanies many neurodegenerative diseases; it is characteristic for Parkinson’s disease (PD). Treatment of advanced PD often includes deep brain stimulation (DBS) of the subthalamic nucleus. Regarding gait, previous studies have reported non-significant or conflicting results, possibly related to methodological limitations. Objective The objective of this prospective study was to assess the effects of DBS on biomechanical parameters of gait in patients with PD. Methods Twenty-one patients with advanced PD participated in this prospective study. Gait was examined in all patients using the Zebris FDM-T pressure-sensitive treadmill (Isny, Germany) before DBS implantation and after surgery immediately, further immediately after the start of neurostimulation, and 3 months after neurostimulator activation. We assessed spontaneous gait on a moving treadmill at different speeds. Step length, stance phase of both lower limbs, double-stance phase, and cadence were evaluated. Results In this study, step length increased, allowing the cadence to decrease. Double-stance phase duration, that is, the most sensitive parameter of gait quality and unsteadiness, was reduced, in gait at a speed of 4.5 km/h and in the narrow-based gaits at 1 km/h (tandem gait), which demonstrates improvement. Conclusion This study suggests positive effects of DBS treatment on gait in PD patients. Improvement was observed in several biomechanical parameters of gait.